Konsep Dan Metode Ijtihad Dalam Islam: Sumber Penting Dalam Pengembangan Hukum Islam - Imana, Yudi; Sucipto, Imam (An-Nisa: Journal of Islamic Family Law, 2024)
The purpose of this research is to analyze the concept and method of ijtihad in Islam as an important source in the development of Islamic law. The method used in this research is a qualitative approach with a literature review of various classical and contemporary sources that discuss ijtihad, including books, scientific articles, and other scientific works. The results show that ijtihad is an intellectual effort made by a mujtahid to produce new laws based on the interpretation of the Qur'an and Hadith when no clear provisions are found in the two sources. The ijtihad method consists of various approaches, such as qiyas (analogy), istihsan (legal preference), and istislah (general maslahah). Ijtihad plays an important role in the adaptation of Islamic law to changing times, as well as providing space for legal novelty in dealing with contemporary issues. This study concludes that ijtihad is not only a legal method, but also a dynamic mechanism that allows the development of Islamic law in accordance with the needs of society.